Wavelet analysis of chaotic time series - J. S. Murguía (Revista Mexicana de Física, 2006)
In this work we analyzed experimental chaotic time series data from three known chaotic systems using the orthogonal wavelet transform.The experimental electronic implementation of the chaotic systems was used to analyze them. The wavelet analysis of the experimentalchaotic time series, with a simple statistical approach, gives us useful information of such systems through the energy concentration atspecific wavelet levels.